Development of a new active drag evaluation system (ADES) - Bideau, B.; Colobert, B.; Fusco, N.; Multon, F.; Delamarche, P. (2002)
The concept of active drag is very important in swimming research area. It is possible to classify the active drag (AD) studies in two main categories: indirect and direct methods. Indirect methods focus on the evaluation of propulsive forces to obtain the AD [2]. Direct methods enable to directly achieve AD. In this way Kolmogorov SV and Duplisheva OA [1] developed an active drag evaluation system. The theoretical basis of this study is used to implement the ADES system. Nevertheless, if the theoretical aspects are well known and controlled, problems arise from the practical application, the drag of the hydrodynamic body applied to the swimmer involves an uncertainty of measurement. The aim of this study was to developed a new system with a good accuracy of the load applied and of the instantaneous speed measurement. METHODS The ADES system (Active Drag Evaluation System) has to comply with Kolmogorov study`s requirements: the load applied on the swimmer must be constant, adjustable (0 to 100 Newton) and measured all along the trial. Data acquisition and post-treatment are performed by a portable computer. A dedicated software has been developed for the ADES system available data are converted and displayed as speed curves, active drag and Cx. A high data acquisition frequency (100 Hz) guarantees a good accuracy of speed variations. RESULTS: With our system we obtained the speed fluctuations (see figure1). Moreover we could computed AD for any kind of swimmers, for example breaststroke swimmers (S) and finswimmers (F). These measurements were made with a good accuracy of the applied load, less than 6% of variation and the swimmers velocity, estimated to 6.10-3 m.s-1 (see table1).